Fisiologia, antropometria e escolarização: práticas discursivas e lutas de representações na Educação Física em impressos entre as décadas de 1930 e 1940 - Rocha, Fabiano Ayub (2022)
It analyzes how the theme of Physiology circulated in the pedagogical and varieties press of Physical Education and how the actors and authors of the period, from 1930 and 1940, sought to use this knowledge and the sub-themes that support it to guide the field of Physical Education. It aims to identify the struggles of representations in the printed materials and to understand how the didactic transposition of the discourses and practices of the physiological sciences was carried out for the school uses that sought to signify Physical Education in the space of schooling. It takes as a reference the development of the French method as a pedagogical project, it was created at the end of the 19th century and beginning of the 20th century. Methodologically, it uses the concept of struggles of representations (Chartier), tactics, strategy and consumption (Certeau), the indicative paradigm (Ginzburg) and the document criticism (Bloch), to show the circulation and appropriation movement of the discourses about Physiology and its school uses. As sources, we used printed materials such as Regulation No. 7 and the pedagogical and variety printed materials that circulated between the 1930s and 1940s, as well as the Ordinances and Decrees that regulated the action plan of the school subjects. As a hypothesis, we work with the possibility that the materials produced on the themes of Physiology, and published in the magazines, circulated as a device to respond a concern expressed in Regulation No. 7, which is that there would be difficulty, on the part of teachers, to appropriate the scientific and pedagogical propositions that the manual presented for the guidance of the new school culture of Physical Education, which caused several printed materials to be created, from 1932 on, to mediate between the official guidance and the teachers in their teaching and evaluation activities. We conclude that the school uses of Regulation No. 7 was not a peaceful point among the intellectuals of the period, many actors tried to become protagonists of the process of didactic transposition of the scientific theories in projects of orientation of the teachers` practices, occurring a fight of representations among authors who had different proposals about the uses of anthropometric and physiological exams for the classification of students, the organization of classes and the execution of the Physical Education classes, in the newly created educational system implemented by Getúlio Vargas and his ministers.